Creatividad y desarrollo cognoscitivo (Un enfoque vigotskyano) - Beatriz Badilla-Baltodano (Universidad Nacional, Costa Rica, 2007)
Development of creativity in university classrooms is of great need in present times, when theoretical knowledge is only part of the formation that a future professional must have. University teachers must be aware that creativity can be fomented and stimulated during college education, therefore, it is an important part of his/her role as an educator. In the present work, development of creativity is explained, based on the schemes established by Vigotsky, Lev Semyónovich who has established the foundations for developing these abilities.